Continuing Professional Development: Issues Raised by Nurses and Allied Health Professionals Working in Musculoskeletal Settings. (24th September 2012) - Haywood, Hannah; Pain, Helen; Ryan, Sarah; Adams, Jo
Abstract: Background: Nurses and allied health professionals (AHPs) are required to evidence their engagement in continuing professional development (CPD) in order to retain their professional registration. Many challenges to CPD are reported, but little literature has explored pertinent CPD issues for clinicians with specialist roles or working in specialist services. No literature to date has explored the perceptions of CPD held by patients who receive these specialist services. Methods: Three focus groups and two conference calls were conducted with nurses, physiotherapists, podiatrists and occupational therapists who work in musculoskeletal (MSK) services; managers of these services; and people who use MSK services. These focus groups aimed: to explore the CPD needs and issues for this group of clinicians; to explore the perceptions of CPD held by people who have MSK conditions; and to compare the above with current literature to discern any factors specific to MSK settings. The focus groups and conference calls were audio‐recorded. The recordings were coded by the researchers using a priori and inductive coding. Results: The main issues discussed were: funding and time for CPD, providing examples of ways to provide CPD in spite of the challenges faced; that CPD needs changed with level of experience; initiatives by clinical specialists to reduce professional isolation; and future trends in CPD, including concerns about succession planning. The views of people with MSK conditions demonstrated an emphasis on communication skills that was seldom raised by managers and clinicians. Conclusions: Sufficient time, funding and provision of study leave were key to facilitating CPD activity for nurses and AHPs working in MSK services. People with MSK conditions particularly valued health professionals who combined good listening and communication skills with an attempt to understand what it was like to live with their condition. Copyright © 2012 John Wiley & Sons, Ltd.